Adolescent exposure to cocaine increases anxiety-like behavior and induces morphologic and neurochemical changes in the hippocampus of adult rats. (28th January 2016) - Zhu, W.; Mao, Z.; Zhu, C.; Li, M.; Cao, C.; Guan, Y.; Yuan, J.; Xie, G.; Guan, X.
Highlights: Adolescent exposure to cocaine increases anxiety-like behavior in adult rats. Adolescent exposure to cocaine impairs pyramidal neurons and increases activities of astrocytes in adult hippocampus. Adolescent exposure to cocaine alters status of synaptic transmission, apoptosis, and inflammation in adult hippocampus. Adolescent exposure to cocaine changes the levels of addiction-related proteins in adult hippocampus. Abstract: Repeated exposure to cocaine during adolescence may affect both physical and psychological conditions in the brain, and increase the risk of psychiatric disorders and addiction behaviors in adulthood. Adolescence represents a critical development period for the hippocampus. Moreover, different regions of the hippocampus are involved in different functions. Dorsal hippocampus (dHP) has been implicated in learning and memory, whereas ventral hippocampus (vHP) plays an important role in emotional processing. In this study, the rats that were exposed to cocaine during adolescence (postnatal days, P28–P42) showed higher anxiety-like behavior in the elevated plus maze test in adulthood (P80), but displayed normal spatial learning and memory in the Morris water maze test. Furthermore, repeated exposure to cocaine during adolescence lead to alterations in morphology of pyramidal neurons, activities of astrocytes, and levels of proteins that involved in synaptic transmission, apoptosis, inflammation and addiction in both dHP and vHP of adult rats. These findings suggest that repeated exposure to cocaine during adolescence in rats may elicit morphologic and neurochemical changes in the hippocampus when the animals reach adulthood. These changes may contribute to the increased susceptibility for psychiatric disorders and addiction seen in adults.